(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the necessity of developing transversal competencies for future technological education teachers based on an integrative approach within the higher education process. It highlights the importance of forming high-level knowledge, skills, and competencies, as well as creating pedagogical and psychological conditions. During the research process, qualitative and quantitative methods related to the development of the components of transversal competencies were effectively utilized, along with educational software tools. Surveys and interviews were conducted in accordance with an education system that aligns with the needs of a developing society. The results indicate that the integrative approach significantly enhances students’ competencies in problem-solving, teamwork, and critical thinking. Furthermore, the collaborative activities of teachers and students facilitate the application of innovative methods in the educational process. The conclusions suggest that the integrative approach plays a crucial role in developing students’ interpersonal relationships and creative thinking, aiding their future professional success. The necessity of expanding such an approach within the education system is also emphasized. Today, the primary goal of universities is not only to provide specialists for society but also to meet all societal needs, utilize digital technologies, create flexibility and creativity in the labor market, and prepare specialists capable of working in teams with intercultural knowledge